2009
DOI: 10.4162/nrp.2009.3.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Folate nutrition is related to neuropsychological functions in the elderly

Abstract: We investigated the nutritional state of B vitamins and the neuropsychological functions in 25 subjects, aged 63.1 ± 6.3 years, residing in rural areas of Korea. Nutritional states of thiamin, riboflavin, and pyridoxine were assessed enzymatically in the erythrocytes, and folate concentrations were measured microbiologically in the plasma and erythrocytes. A battery of composite neuropsychological test was administered to the subjects. Plasma folate was correlated with the total intelligence score (p=0.049). F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Similar to our previous findings, GCPII +/- control mice are less social than wildtype control mice (Han et al, 2009). Similar to studies in other laboratories, our wildtype folate deficient mice have impaired motor coordination and spatial memory (Troen et al, 2008; Chang et al, 2009). Additionally, we show that folate-deficient male mice exhibit decreased sociability, similar to the GCPII heterozygotes.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to our previous findings, GCPII +/- control mice are less social than wildtype control mice (Han et al, 2009). Similar to studies in other laboratories, our wildtype folate deficient mice have impaired motor coordination and spatial memory (Troen et al, 2008; Chang et al, 2009). Additionally, we show that folate-deficient male mice exhibit decreased sociability, similar to the GCPII heterozygotes.…”
Section: Discussionsupporting
confidence: 88%
“…Affective Drugs Some drugs and vitamins are known to affect mental performance and alertness. For example, antihistamines, antidepressants, and antianxiety drugs may make a person less alert [White and Rumbold 1988] whereas some recreational drugs and vitamins may help increase performance intelligence [Chang et al 2009]. …”
Section: Skin Colormentioning
confidence: 99%
“…5 Among B vitamins, thiamine has received much attention as previous studies indicate a close association between thiamine deficiency and neurological abnormalities including cognitive dysfunction, anxiety, and delirium. [6][7][8][9][10] Cross-sectional analyses of 611 nondemented elderly patients (aged 72.3 [5.9] years) demonstrated a positive correlation between blood thiamine diphosphate, the most bioactive form of thiamine, and cognitive function. 9 However, in a study of 25 Korean elderly patients (mean age: 63.1 [6.3] years), no significant association between blood thiamine levels and neuropsychological function was observed.…”
Section: Introductionmentioning
confidence: 99%
“…9 However, in a study of 25 Korean elderly patients (mean age: 63.1 [6.3] years), no significant association between blood thiamine levels and neuropsychological function was observed. 6 In addition, depression is one of the most frequent psychiatric diseases in older individuals and is associated with impairment in physical function, emotional symptoms, and quality of life. 4,11 Review of previous literature demonstrated that thiamine deficiency may be related to mood disorders and depression.…”
Section: Introductionmentioning
confidence: 99%